Enzyme hydrolysates from stichopus horrens as a new source for angiotensin-converting enzyme inhibitory peptides - Forghani B.; Ebrahimpour A.; Bakar J.; Abdul Hamid A.; Hassan Z.; Saari N. (2024)
Indexed by WOS/ Scopus